Longitudinal demographic study of wild populations of African annual killifish - Vrtílek, Milan; Žák, Jakub; Polačik, Matej; Blažek, Radim; Reichard, Martin (Scientific reports, 2018)
The natural history of model organisms is often overlooked despite its importance to correctly interpret the outcome of laboratory studies. Ageing is particularly understudied in natural populations. To address this gap, we present lifetime demographic data from wild populations of an annual species, the turquoise killifish, Nothobranchius furzeri, a model species in ageing research, and two other species of coexisting annual killifishes. Annual killifish hatch synchronously, have non-overlapping generations, and reproduce daily after reaching sexual maturity. Data from 13 isolated savanna pools in southern Mozambique demonstrate that the pools supporting killifish populations desiccated 1-4 months after their filling, though some pools persisted longer. Declines in population size over the season were stronger than predicted, because they exceeded the effect of steady habitat shrinking on population density that, contrary to the prediction, decreased. Populations of N. furzeri also became more female-biased with progressing season suggesting that males had lower survival. Nothobranchius community composition did not significantly vary across the season. Our data clearly demonstrate that natural populations of N. furzeri and its congeners suffer strong mortality throughout their lives, with apparent selective disappearance (condition-dependent mortality) at the individual level. This represents selective force that can shape the evolution of lifespan, and its variation across populations, beyond the effects of the gradient in habitat persistence.
Keywords: Animals; hustota populace; Population Dynamics; populační dynamika; zvířata; longitudinální studie; Sex Ratio; Longitudinal Studies; dlouhověkost; Sympatry; sympatrie; Longevity; Population Density; Seasons; Female; poměr pohlaví; Male; ekosystém; Ecosystem; roční období; Cyprinodontiformes; ženské pohlaví; mužské pohlaví